Optimization and validation of LAMP technique for the detection of leptospiral DNA - Hamer, Micaela; Saraullo, Vanina Rosa; Esteban, Micaela; Sanchez, Maria Cristina; Brihuega, Bibiana Felicitas; Martinez, Mara Leila (International Leptospirosis Society, 2024)
Poster